Lung Change Pattern On Domestic Cat (Felis Silvestris Catus) Exposed By Factory Air Pollution With X-Ray Thorax Interpretation - Ratna Widyawati; Desty Apritya; Junianto Wika Adi Pratama; Asnizar Fahmi (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
The pathology density changes for X-Ray interpretation of the lungs are difficult to distinguish, because the  disease is not easily classified and may represent a variety of lung disorders. The study was aimed of this research to found the lung disease of domestic cats (Felis Silvestris Catus) that exposure to air pollutions in the industrial area of region Manyar, district Gresik. The type of this research was observational study Explorative that using the simple random sampling and observed nine cats for the sampling.The results of X-ray Thorax in this research showed that there are changing in the 3rd, 4th, 5th, 6th, 7th, an 9th of the sampling cats. On the third, fifth and the seventh of the cats, we found the same condition that there was change the vascular patterns that were enlargement, vascular constriction or ambiguity structures. From the results of the vascular patern indicate the disorder of left-sided heart failure (Mitral Isufisiency) or obstruction of the left atrium. On the fourth of the cat, there was bronchial pattern that showed the classification, dilatation and thickness of the lung. On the sixth of the cats, there were changes on interstitial pattern with the pictures of nodulars that were not structures and on the ninth of the cats, we can found the same conditions with the fourth and the sixth of cats were visible Interstitial Pattern and Bronchial Interstitial Pattern.